Estudos moleculares da Selenocisteína Sintase (SELA) de Escherichia coli - Cassago, Alexandre (Universidade Federal de São Carlos, 2005)
The study of translation processes attracts the interest of a wide range of research groups due to its main role in general cellular metabolism. In particular, the investigation of new amino acid residues, such as selenocysteine and pyrrolysin, which result in an expansion of the genetic code from the traditional 20 residues to a total of 22 residues up to the current time. The amino acid, selenocysteine represents the main biological form of the selenium element and its synthesis and co-translational incorporation into selenoproteins are due to an in-frame UGA stop codon using complex molecular machinery. On Escherichia coli, the main proteins involved in this pathway are: Selenocysteine Synthase (SELA), Selenocysteine Elongation Factor (SELB or EFSec), Selenophosphate Synthetase (SELD) and a tRNAsec uca specific for this pathway named Selenocysteine Insertion tRNA (SELC). The SELA protein, the subject of this study, was firstly purified by Forchhammer in 1991 and the sole structural analysis realized to this day was developed by Engelhardt in 1992, using the Scanning Transmission Electron Microscope (STEM) technique. With a monomer of approximately 50kDa, SELA assumes an homodecamerical spatial configuration, each dimmer capable of binding to a tRNAsec uca with the serine amino acid which will be converted in selenocysteine, in a reaction dependant of the enzymatic cofactor piridoxal 5 fosfato. On this work it was possible to develop a new purification protocol for the SELA protein, considerably reducing the steps and consequently the time involved for obtaining purified protein. The process also yielded better protein production when compared to literature, from 1mg/ml starting with 10 liters to approximately 4.5mg/ml starting with 3 liters of bacterial medium. As for the structural experiments, it was possible to predict by Dynamic Light Scattering (DLS) the molecular mass as about 442kDa, Circular Dichroism (CD) predicted the secondary structure as mainly composed by α-helices and Small Angle X-ray Scattering (SAXS) showed the global structure of SELA with a maximum diameter of 185Å, a molecular mass of about 527kDa and a radius of gyration of 67.3 Å
Keywords: Biologia molecular; Selenocisteína Sintase; Selenocisteína; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS